2003
DOI: 10.1099/vir.0.18501-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of glyceraldehyde-3-phosphate dehydrogenase with secondary and tertiary RNA structural elements of the hepatitis A virus 3′ translated and non-translated regions

Abstract: Proteins interacting with RNA structures at the 39 non-translated region (39NTR) of picornaviruses are probably important during viral RNA replication. We have shown previously that a dominant cellular cytoplasmic protein of 38 kDa (p38) interacts with the 39NTR and upstream regions of the hepatitis A virus (HAV) RNA (Kusov et al., J Virol 70, 1890-1897. Immunological and biochemical analyses of p38 have indicated that it is identical to GAPDH, which has previously been described as modulating translational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…This effect was abolished when the protein was pretreated with oxidant GSSG, a condition shown to covalently modify Cys 152. Published works have already reported that binding of GAPDH to AU-rich stem-loop structures results in the loss of double-stranded-RNA regions (15,47). We hypothesize that GAPDH may function as an RNA anti-chaperone protein, promoting by RNA unwinding and hence facilitating the degradation of RNA by additional cellular components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was abolished when the protein was pretreated with oxidant GSSG, a condition shown to covalently modify Cys 152. Published works have already reported that binding of GAPDH to AU-rich stem-loop structures results in the loss of double-stranded-RNA regions (15,47). We hypothesize that GAPDH may function as an RNA anti-chaperone protein, promoting by RNA unwinding and hence facilitating the degradation of RNA by additional cellular components.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of GAPDH binding to AU-rich RNAs have described rearrangements of the RNA structure, with the loss of double-stranded-RNA regions upon interaction (15,47). It is therefore plausible to hypothesize that GAPDH interaction with ET-1 mRNA facilitates the degradation of the mRNA by modification of the RNA structure at the 3Ј UTR, making it more susceptible to attack by cytosolic ribonucleases.…”
mentioning
confidence: 99%
“…The 3Ј NCRs of some viruses have been shown to interact with host proteins (4,28,40). Therefore, given the extent of differences between strains Sar55 and Meng in these regions, it appeared reasonable to determine whether the Sar/3Јswine chimera could infect pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The 3Ј NCR of viruses has been reported to interact with host proteins (4,28,40), and since there was a 26% difference in nucleotide sequence in this region between strains Sar55 and Meng, it seemed possible that this region might be responsible for the ability of the swine virus to infect different species. To test this hypothesis, we made one virus pool containing HEV from a rhesus monkey that had been transfected with transcripts synthesized in vitro from pSar55 and another virus pool from a monkey that had been transfected with transcripts synthesized in vitro from pSar/3Јswine; we inoculated approximately 10 6 genomes of Sar55 or of Sar/3Јswine into swine.…”
Section: Vol 79 2005mentioning
confidence: 99%
“…The presence of two enzymes involved in glycolysis (phosphofructokinase C and glyceraldehyde-3-phosphate dehydrogenase) in an mRNP preparation was not expected but may support the assumption that there exists a link between glycolysis and the protein synthesis machinery (26). Thus the product of the phosphofructokinase, fructose 1,6-bisphosphate, acts as a stimulant of mRNA translation (27), whereas the glyceraldehyde-3-phosphate dehydrogenase may affect mRNA translation via its know ability to bind viral mRNAs (28,29).…”
Section: Figmentioning
confidence: 99%